In silico design novel vibsanin B derivatives as inhibitor for heat shock protein 90 based on 3D-QSAR, molecular docking and molecular dynamics simulation. Issue 14 (21st September 2020) - He, Qingxiu; Chu, Han; Wang, Yuxuan; Guo, Haiqiong; Wang, Yuanqiang; Wang, Siyi; Feng, Zhiwei; Xie, Xiang-Qun; Hu, Yong; Liu, Haibin; Lin, Zhihua
Abstract: Communicated by Ramaswamy H. Sarma